PERMAINAN KARTU SEKATA TERHADAP PEMAHAMAN KOSAKATA SISWA KELAS II DI SEKOLAH DASAR - Yulaikah, Anik; Cholifah Tur Rosidah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research was motivated by students' difficulties in retaining and understanding vocabulary meanings over time, as well as the lack of variation in teaching methods and media, which caused students to become easily bored, less active, and unfocused during learning. The aim of this study was to determine the effect of the